A Study on Spiritual Quotient Among College Students In Coastal Town of Mangalore, Karnataka State. - Dr.Epari Ravi Kiran, Dr.Karri Vijaya, (International Journal of Scientific Research and Management (IJSRM), 2015)
The present study aims to assess the spiritual quotient of college students in Mangalore City. Twocollegewere selected by simple random sampling. About 100 students were selected from each of thecolleges takenup for the study. Majority of the students fall in average SQ category (83.88% ). 21.1 % ofstudents fall inhigh category. Medical students had a statistically significant higher mean score compared tothat of thedegree college students . Mean SQ of the female students was more than males and it wasstatisticallysignificant. Jain and sikh students had a better score. In the self improvement test wheresituations werepresented before students, Christians scored highest (72.86%).